Kajian Hermeneutika Tentang Ketidaktahuan Yesus Mengenai Kedatangan-Nya Yang Kedua Kali Berdasarkan Markus 13:32 Dan Implikasi Nya Bagi Ajaran Kristologi - Nunuhitu, Petra A.; Panggarra, Robi; Lele, Aldorio F.; Dju, Nyoman Lisias F. (Jurnal Kala Nea, 2022)
Abstract This study aims to analyze and discover about Jesus' ignorance regarding the second coming. In addition, in writing this scientific paper, a description of the implications of this ignorance of Christology will also be included. In an effort to obtain these objectives in this study, researchers use The research method used in writing this thesis is a qualitative research method based on hermeneutic principles with a commonly used interpretation approach described by Hasan Sutanto. This approach focuses on the text of Mark 13:32. Next, the author uses data collection techniques through library research by using the Bible as primary literature and dictionaries, interpretations, books and journals as secondary literature.   The results showed that Jesus said the Son did not know the second coming does not mean that He  really did not know the  coming,  Jesus knew of the day but He limited Himself to not knowing that day at once this is a statement that man is limited, and as a Son He chose to obey the Father's plan for Himself in the first coming.